The Caribbean Catastrophe Risk Insurance Initiative : A Review of CCRIF's Operation After Its Second Season - World Bank (Washington, DC, 2014)
This report provides an external assessment of the operations of the Caribbean Catastrophe Risk Insurance Facility (CCRIF) during its second policy year from June 1, 2008 to May 31, 2009. Developed at members and associate members of the Caribbean Community (CARICOM's) request following the devastation wrought on Grenada and the Cayman Islands by Hurricane Ivan in 2004, CCRIF was established in May 2007. The World Bank and a number of donors contributed to CCRIF's start-up capital and also underwrote a portion of some members' initial participation fees and premium payments during CCRIF's first three policy years. A multi-donor trust fund continues to reimburse CCRIF for certain eligible expenditures, thus facilitating continued growth of CCRIF's reserves and risk-bearing capacity. The report aims to contribute to on-going discussions within the broader disaster risk management community about the possibilities for scaling up the role of CCRIF in the Caribbean and replicating or adapting CCRIF's innovative model of ex ante disaster risk financing in other disaster-prone regions of the world. Rolling out the second-generation loss model, the anticipated excess rainfall coverage and, possibly, hurricane loss coverage for members of Caribbean Association of Electrical Utilities (CARILEC) will require intensive interactions with CCRIF's members, reinsurance markets, key partner institutions, and the media to ensure a common understanding of the model and the features, inherent basis risk, and benefits of the policies. Increasing CCRIF's transparency is also vital to broadening understanding of CCRIF's governance structure, modeling, and policy coverage and consolidating CCRIF as a well-recognized and widely-valued Caribbean institution.